DEVELOPMENT OF INTERACTIVE MAPS FOR THE NEEDS OF TOURISM - Дудун, Тетяна; Ліпавський, Ілля (SWorldJournal, 2023)
The relevance of the creation and development of interactive maps for the needs of tourism is substantiated, the object of the research is defined. Analyzed software used to create interactive maps for tourism needs. The requirements are defined and metho